Investigation of domain kinetics in congruent lithium niobate modified by proton exchange. Issue 1 (27th May 2016) - Neradovskiy, M. M.; Shur, V. Ya.; Mingaliev, E. A.; Zelenovskiy, P. S.; Ushakova, E. S.; Tronche, H.; Baldi, P.; De Micheli, M. P.
ABSTRACT: The domain structure evolution has been studied in congruent lithium niobate crystals with surface layers modified by three different proton exchange techniques. The significant decrease of the nucleation threshold field and qualitative change of domain rays nucleation and growth have been revealed. The formation of a broad domain boundary and dendrite domain structure as a result of nanodomains merging in front of the moving rays has been demonstrated. The obtained effects have been attributed to features of the domain kinetics induced by built-in electric field and retardation of the bulk screening of depolarization field.